Ovarian collision tumour consisting of a fibroma and a serous cystadenoma: A case report - Anwar Rjoop; Rawan Obiedat; Ayat Al-Oqaily; Shaden Abu Baker; Ismail Matalka (Elsevier, 2024)
This article reports a case of an ovarian collision tumour consisting of an ovarian fibroma and a serous cystadenoma. A 60-year-old woman exhibited symptoms of post-menopausal bleeding and abdominal pain persisting for three months. Computerized tomography identified a solid mass with a cystic component in the right adnexa, and the patient underwent staging laparotomy. Gross examination of the right ovary revealed a cystic tumour with adjacent solid mass. The histopathological analysis identified a cystic mass that matched the characteristics of a serous cystadenoma, with an adjacent solid mass that matched the characteristics of a sex-cord stromal tumour, both located in the right ovary. Additionally, a small cyst that matched the characteristics of a serous cystadenoma was found in the left ovary. There have been only seven previously reported examples of this specific mix of ovarian tumours. Mostly affecting patients above 60 years of age, although tumour markers levels are normal, such cases may present with a complex clinical scenario, as in this case, and demand a comprehensive diagnostic and therapeutic approach.